Utilization trend of gastric acid-suppressing agents in relation to analgesics - Kırmızı Sönmez, Neriman İpek; Aydın, Volkan; Akıcı, Ahmet (Wiley, 2022)
Background: Controversies exist about excessive use of gastric acid-suppressing agents or lack of adequate indications, especially when co-prescribed with analgesics for gastroprotection. We aimed to analyze the nationwide trend of gastric acid-suppressing agents and analgesics. Methods: We obtained nationwide consumption data of analgesics (nonsteroidal anti-inflammatory drugs [NSAIDs], opioids, others) and gastric acid-suppressing agents (proton pump inhibitors [PPI] and histamine-2 receptor antagonists [H2RAs]) between years of 2014–2018 from IQVIA Turkey. Drug utilization was measured by defined daily dose (DDD)/1000 inhabitants/day (DID) unit. Drug sales data were further used to test the correlation of PPIs and H2RAs to analgesics. Results: During the study period, analgesic utilization increased from 65.7 to 67.4 DID. NSAIDs constituted 82.7%–84.9% of all analgesic utilization. The consumption of NSAIDs increased by 3.1%, and the most commonly consumed analgesic was diclofenac (18.5 ± 1.5 DID), constituting 25.4%–29.0% of all analgesics. PPI utilization was found to regularly raise from 52.1 DID in 2014 to 72.0 DID in 2018 with an overall increment of 38.2%. Use of H2RAs was found to increase from 11.4 DID in 2014 to 14.0 DID in 2018. The physician visit-adjusted utilization of both antirheumatic NSAIDs and non-antirheumatic analgesics showed significantly moderate-strong positive correlations with PPIs (r: 0.63, 0.48–0.76 and r: 0.63, 0.47–0.75, respectively) and H2RAs (r: 0.61, 0.44–0.73 and r: 0.57, 0.41–0.71, respectively). Conclusion: The utilization trend exhibited a dramatic increase of the gastric acid-suppressing agents -more pronounced for PPIs, with a modest increase in analgesics. Excessive utilization of PPIs does not seem to imply a tendency toward only NSAID-related gastroprotection.
Keywords: Analgesics; Diclofenac; Gastric Acid-Suppressing Agents; Pantoprazole; Ranitidine; Utilizationtrend